202 IMPACT OF METABOLIC SYNDROME ON LEFT VENTRICULAR MASS AND GEOMETRY IN YOUNG ADULTS: THE BOGALUSA HEART STUDY. Issue 1 (1st January 2007) - Patel, D. A.; Srinivasan, S. R.; Chen, W.; Berenson, G. S.
Abstract : Background: The geometric patterns of left ventricular hypertrophy (LVH) are of incremental importance to the magnitude of left ventricular (LV) mass as a predictor of cardiovascular (CV) risk. However, the role of metabolic syndrome, a constellation of CV risk factors, affecting LV mass and geometry in an otherwise healthy young adult population is unclear. Methods: This aspect was examined in 830 asymptomatic individuals (mean age 36.5 years, 68.5% whites, 41% males) as part of the Bogalusa Heart Study. LV parameters were assessed by two-dimensional M-mode echocardiography according to the American Society of Echocardiography recommendations. Relative wall thickness was calculated as septal wall thickness plus posterior wall thickness divided by LV end-diastolic diameter. Results: Individuals with metabolic syndrome (as defined by the National Cholesterol Education Program ATP III) showed significantly higher LV mass, LV mass index, end-diastolic posterior wall thickness, septal thickness, relative wall thickness, LV end-diastolic diameter, and lower fractional shortening and E/A ratio than individuals without metabolic syndrome. With respect to metabolic syndrome components, individuals with eccentric or concentric hypertrophy showed higher values of metabolic syndrome risk factors compared with individuals with a normal geometric pattern, but no differences were noted between individuals with normal and concentric remodeling pattern of LVH. Of note, individuals with concentric versus eccentric hypertrophy showed significantly higher mean arterial blood pressure and insulin resistance index (HOMA-IR). LV mass index and relative wall thickness were significantly correlated to all components of metabolic syndrome. Moreover, after adjusting for age, race, gender, and antihypertensive medication use, metabolic syndrome was associated with a sixfold increase in LV mass index and a 2.6- fold increase in relative wall thickness; these associations remained significant even after adjusting for individual components of metabolic syndrome. Further, LV mass index and relative wall thickness increased with increasing number of metabolic syndrome risk factors, regardless of age, race, and gender ( p for trend, < .0001). Conclusion: Metabolic syndrome is strongly related to LV mass and geometric patterns and exerts more adverse influence on LV structure than each of its components alone.